Sosiopat di Lingkungan Sosial dalam Karya Seni Grafis Relief Print - Fadhel Muhammad Ansyory; Ariusmedi Ariusmedi (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The purpose of the final work is to visualize the characteristics of antisocial traits in order to increase knowledge about antisocial traits and avoid them. The method of creation carried out in the final work has stages from the beginning of the process to the end, namely the preparation, elaboration, synthesis, concept realization, and completion or finishing stages in the work. In the process of making the final work measuring 50 cm x 40 cm using the Filter Printing technique, there are 10 pieces with the titles namely: Sharp Gaze, Charismatic, Impulsive, Foothold, Liar, No Regrets, Wolf in Sheep's Clothing, Manipulator v.1, Manipulator v.2, Manipulator v3.